2012
DOI: 10.1155/2012/461592
|View full text |Cite
|
Sign up to set email alerts
|

Cognitively Stimulating Activities: Effects on Cognition across Four Studies with up to 21 Years of Longitudinal Data

Abstract: Engagement in cognitively stimulating activities has been considered to maintain or strengthen cognitive skills, thereby minimizing age-related cognitive decline. While the idea that there may be a modifiable behavior that could lower risk for cognitive decline is appealing and potentially empowering for older adults, research findings have not consistently supported the beneficial effects of engaging in cognitively stimulating tasks. Using observational studies of naturalistic cognitive activities, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
66
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 26 publications
8
66
1
4
Order By: Relevance
“…To our knowledge this finding has not been reported elsewhere, but associations between correlated change in physically and cognitively demanding recreational activity and cognition have been documented previously (e.g. Lindwall, et al, 2012; Mitchell, et al, 2012). Replication of our finding in an independent sample is warranted.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…To our knowledge this finding has not been reported elsewhere, but associations between correlated change in physically and cognitively demanding recreational activity and cognition have been documented previously (e.g. Lindwall, et al, 2012; Mitchell, et al, 2012). Replication of our finding in an independent sample is warranted.…”
Section: Discussionsupporting
confidence: 65%
“…However, not all studies have found protective effects of recreational activity on longitudinal cognitive change (e.g. Mitchell, et al, 2012). Evidence of correlated change in leisure activity and cognition suggests that associations between recreational activity and cognition may be best characterized longitudinally (Lindwall, et al, 2012; Mitchell, et al, 2012).…”
mentioning
confidence: 99%
“…More negative cognitive change at older ages has been reported in many studies (e.g., Lamar et al, 2003; Mitchell et al, 2012; Parisi et al, 2011; Ronnlund & Nilsson, 2006; van Dijk et al, 2008). A few studies have reported differential change in males and females (e.g., Parisi et al, 2011), but there are also numerous reports of no sex differences in change (e.g., Finkel et al, 2003; Lamar et al, 2003; Lovden et al, 2004), or mixed patterns in different cognitive variables (e.g., Mitchell et al, 2012; van Dijk et al, 2008).…”
Section: Potential Correlates Of Changementioning
confidence: 65%
“…8,9 Although findings on the effects of a healthy lifestyle on later life outcomes are generally encouraging, the type and amount of activity needed to confer such benefits remains poorly understood. In addition, there is great variation in activity patterns across individuals, with some individuals focusing all of their time and efforts on a few select activities and others allocating their time across many different contexts.…”
mentioning
confidence: 99%